Platelet-To-Lymphocyte Ratio as a Predictor of Disability Prognosis in Acute Ischemic Stroke Patients at Bethesda Hospital - Bagaskara, Arya T; Pinzon, Rizaldy; Mitasari, Pradita S (Journal of Medicine and Health, 2025)
Stroke precipitates a neuroinflammatory response. Platelet-to-lymphocyte ratio (PLR) is an inflammatory biomarker conveying plaque adhesion and infarct volume. A high level of PLR is associated with stroke patient’s poor clinical outcomes. This study highlights PLR's potential as a predictive biomarker for post-stroke disability. This study aims to measure PLR at admission and to investigate its potential as a predictor for post-stroke disability. A retrospective cohort study was designed with 98 subjects from Bethesda Hospital Yogyakarta. ROC/AUC analyzed PLR to find the optimal cut-off value. Risk factors were analyzed to find the correlation and causality. From 98 patients, the optimal PLR cut-off is 146.86. A significant positive correlation was observed between PLR and modified Rankin Scale (mRS) scores (p=0.017), and National Institutes of Health Stroke Scale (NIHSS) scores (p=0.043). A significant mean difference in PLR values was also identified between mRS outcomes (p=0.017). PLR was a predictor for mRS (OR=4.051, p=0.037), although it did not predict NIHSS outcomes. The findings indicate that PLR is predictive of post-stroke disability in cases of ischemic stroke. An elevation in PLR suggests a disequilibrium between inflammatory mediators and neuroprotective factors. In conclusion, PLR has the potential as a predictor for post-stroke disability in ischemic stroke